KAJIAN KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN DI LINGKUNGAN UNIVERSITAS SAMUDRA - Rosalina, Dhian; Zati, Muhammad Rizqi; Ardiyanti, Dyah Ayu (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2016)
The  quality  of  academic  services  is  a  comparison  between  the  perceived  academic service  customers  or  stakeholders  with  the  quality  of  academic  services  that diharapkanpelanggan.  The  purpose  of  this  study  was  to  determine  how  the  level  of  student satisfaction on the performance of academic services at the University of the ocean, and identify as to whether the expectations of students as users of our services to academic services at the University of the ocean.The  population  in  this  study  were  all  students  of  both  the  semester  active  maaupun aajaraan  odd  year  2016-2017  as  users  of  services  from  academic  services,  which  the respondents of this activity drawn from five faculties at the University of the ocean environment. Side technique used is proportional stratified random sampling which classifies the populationconsists of five faculties. The method used is the gap analysis that compares the perceptions of respondents mahasiswaa expectations with reality.From  the  results  of  the  study  shows  that,  for  services  such  as  facilities  and  media university  lectures  and  attitude  of  staff  behavior  akademikberdasarkan  student  perceptions require improved performance. While factors  -  other factors such as library facilities, attitudes and behavior of faculty, administrative staff and library responsiveness, competence of lecturers and administrative staff, is perceived quite well by studentsKeywords : service quality, Gap Analysis